Beyond Business : Corporate Social Responsibility (CSR) Among Small Businesses In Jelutong Market, Penang, Malaysia - Wong, Teik Aun (2017)
This study explores the phenomenon of Corporate Social Responsibility (hereinafter abbreviated as “CSR”) among small businesses in Jelutong wet market in Penang, Malaysia. This is a qualitative research employing case study methodology with three (3) data gathering instruments employed namely non-participant observations, semi-structured interviews and participant observations. The selected field site is Jelutong wet market in Penang, Malaysia. The findings show that existing literature on CSR is inadequate to capture and understand it in the context of small businesses in a wet market.